A superior liquid phase catalyst for enhanced absorption of NO2 together with SO2 after low temperature ozone oxidation for flue gas treatment. (1st July 2019) - Shao, Jiaming; Ma, Qiang; Wang, Zhihua; Tang, Hairong; He, Yong; Zhu, Yanqun; Cen, Kefa
Graphical abstract: Highlights: KI additive was found as a liquid catalyst in simultaneous NO2 and SO2 removal. NO x /SO2 removal efficiency was steady in 300 min stability test. Reaction pathways for NO2 /SO2 absorption in KI solution was discussed. Ozone oxidation and KI catalytic absorption is a feasible way in NO x /SO2 treatment. Abstract: NO x and SO2 are the main air pollutants emitted from the coal-fired combustors. Since the typical combination of selective catalytic reduction (SCR) and wet flue gas desulfurization (WFGD) is not suitable for some of industrial flue gas treatment due to their unsuitable temperature window and limited retrofitting space, new technologies must be developed. This paper proposes an effective wet method for simultaneous removal of NO x and SO2 . The insoluble NO was first oxidized into NO2 by ozone, and then NO2 together with SO2 were both absorbed in one wet wash tower. To further improve NO2 removal efficiency, a new kind of additive was proposed and tested. Effects of various influence factors, such as additive concentration, residence time in the wash tower, liquid/gas ratios, initial NO/SO2 /O2 concentration and slurry pH value, were carefully evaluated in a home-designed experimental platform. Results indicated that the NO x removal efficiency was positively correlated with the increasing the additive concentration, while the maximum denitration and desulfurization efficiency were more than 95% and 86%. The NO x removal efficiency was enhanced with the increasing residence time and liquid/gas ratios. The alkaline environment was verified to be beneficial for the simultaneous absorption process. The exiting O2 in flue gas would not consume additives, and the denitration and desulfurization efficiency were insensitive to the initial NO and SO2 concentration as well. Only 2% decrease of the denitration efficiency was observed after 300 mins stability test, while the desulfurization efficiency kept >98%. With the characterizations of Ion Chromatograph (IC), NO2 −, NO3 − and SO4 2− were detected as the main absorption by-products anions, whereas NO2 − accumulation would inhibit the overall NO x removal. Finally, the mechanism of simultaneous removal of SO2 and NO using the novel liquid phase catalyst was proposed and discussed.